Acute-Phase Levels of CXCL8 as Risk Factor for Chronic Arthralgia Following Chikungunya Virus Infection - Jacob-Nascimento, Leile Camila; Carvalho, Caroline Xavier; Silva, Monaíse Madalena Oliveira; Kikuti, Mariana; Anjos, Rosângela Oliveira; Fradico, Jordana Rodrigues Barbosa; Campi-Azevedo, Ana Carolina; Tauro, Laura Beatriz; Campos, Gúbio Soares; Moreira, Patricia Sousa dos Santos; Portilho, Moyra Machado; Martins-Filho, Olindo Assis; et al. (Frontiers in Immunology, 2021)
The immunopathogenesis of chikungunya virus (CHIKV) infection and the role of acute-phase immune response on joint pain persistence is not fully understood. We investigated the profile of serum chemokine and cytokine in CHIKV-infected patients with acute disease, compared the levels of these biomarkers to those of patients with other acute febrile diseases (OAFD) and healthy controls (HC), and evaluated their role as predictors of chronic arthralgia development. Chemokines and cytokines were measured by flow Cytometric Bead Array. Patients with CHIKV infection were further categorized according to duration of arthralgia (≤ 3 months vs >3 months), presence of anti-CHIKV IgM at acute-phase sample, and number of days of symptoms at sample collection (1 vs 2-3 vs ≥4). Patients with acute CHIKV infection had significantly higher levels of CXCL8, CCL2, CXCL9, CCL5, CXCL10, IL-1β, IL-6, IL-12, and IL-10 as compared to HC. CCL2, CCL5, and CXCL10 levels were also significantly higher in patients with CHIKV infection compared to patients with OAFD. Patients whose arthralgia lasted > 3 months had increased CXCL8 levels compared to patients whose arthralgia did not (p<0.05). Multivariable analyses further indicated that high levels of CXCL8 and female sex were associated with arthralgia lasting >3 months. Patients with chikungunya and OAFD had similar cytokine kinetics for IL-1β, IL-12, TNF, IFN-γ, IL-2, and IL-4, although the levels were lower for CHIKV patients. This study suggests that chemokines may have an important role in the immunopathogenesis of chronic chikungunya-related arthralgia.